The Effect Of Managerial Ownership, Independent Commissioner, And Tax Planning On Profit Management In Manufacturing Companies Listed On Indonesia Stock Exchange 2020-2022 - Sari, Putri Zanufa; Suciati, Ajeng Mustika (LPPM of NAROTAMA UNIVERSITY, 2023)
Profit management is an attempt by management to manipulate information so that it does not reflect reality. The purpose of earnings management is to provide information in the form of financial statements that have been manipulated through various efforts to bring produce the financial statements desired by management, in order to provide stakeholders and potential investors with an overview of management's performance in terms of generating company profits. Several factors are considered to influence profit management, namely managerial ownership, independent commissioners and tax planning. The purpose of this research is to analyse the influence between managerial ownership, independent commissioners and tax planning on profit management in manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The type of research used is quantitative research, with a sample of manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique used was purposive sampling technique. The results showed that managerial ownership variable had a negative effect on profit management, independent commissioner variable had no significant effect on profit management, tax planning variable had a positive effect on profit management, and managerial ownership, independent commissioners and tax planning simultaneously affected profit management.